Sexual dysfunction in elderly men and women - Paulina Trawka; Beniamin Szmelcer; Daria Zaborna; Marlena Kontowicz; Martyna Goljat; Mateusz Porada; Klaudia Kwiatkowska; Marcin Falkowski; Agnieszka Nawrocka; Joanna Sarnowska; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2019)
Background: The aging process of the body is inexorable and affects all areas of geriatric patient's life, including the quality of his sex life. In this case, however, also psychological and environmental problems must be taken into account in the case of diagnostics. The sexuality of elderly patients has been neglected by the medical community for many years, and even recognized by some doctors as unnecessary or bad. Currently, there is a slow change in this position, also due to the patients themselves who are looking for help in specific situations. Material and methods: Analysis of available literature, articles in the Google Scholar and PubMed database using keywords: Sexuality, Geriatrics, Dysfunctions Results: Statistics on the sexuality of the elderly give a clear picture of how great a problem this sphere of life is. The main risk factors for sexual dysfunction of the above-mentioned patients include, among others, abnormal lifestyle and urinary tract infections. In the patients' lifestyle the most important aetiological factors are incorrect diet or lack of physical activity. Men of all ages are exposed to problems, however, in the epidemiology of this dysfunction, a drastic jump after the age of 50 is noticed. It is connected with the weakening of the function of the nervous system and microcirculation in the urinary tract and the reduction of the number of hormones responsible for the functioning of sexual organs. In women, this menopause is the period that most destructively affects the quality of sexual life. Here, as in the case of men, a reduced amount of hormones has a negative effect, among others, by a reduced sexual desire or the presence of pain during intercourse. In the treatment of the above-mentioned disorders, mainly pharmacology has the largest field of action. In the treatment of sexual dysfunction, we mainly use 2 compounds and these are sildenafil and tadalafil. Conclusions: Human sexuality, especially in the case of older people, can not be a neglected subject, and dysfunctions and problems of patients treated like any other. The need to integrate interdisciplinary mode in dealing with this type of problems is more necessary. All this is connected with the fact that there is a definite deficit in publications and research on this subject, which creates a wide range of possibilities for the medical community.